Memory and Recalling in Shelagh Stephenson’s The Memory of Water - Kader Güzel (Theatre Academy)
Memory, through which knowledge, memories, and experiences are conserved in mind, is of great importance for the history of humankind. It is not a novel idea that the ability of memory constitutes the human identity and consciousness. Psychological studies, as well as philosophical assumptions, demonstrate the significance of recollection of past events in conducting life and constructing a healthy personality. In light of those preliminary observations, this paper focuses on the historical development of the subject of memory and turning points of memory studies. In addition to the chronological description of memory, how it is evaluated under the effect of historical development as well as the significance of it in the life cycle of human beings is likewise specified in this study. Expressing the thoughts and research of various thinkers and philosophers, this study represents the variable approaches to memory. While discussing Shelagh Stephenson’s award-winning play, The Memory of Water (1996), the central concern is to analyse how subjective and mutual memories have formed and influenced the characters’ lives. The play reveals the portrayal of the prominence of remembering and reminiscing, which are directly related to our constitution of self and well-being. In light of scientific research and the recollections of the characters, the significance of remembering and reminiscing actions that are directly related to our constitution of self and well-being is specified. The play stresses the paramount importance of communicating and sharing among the family members or within a social environment, as misattribution shows up as an imperfection of memory.